NUMERICAL PREDICTION OF INFILTRATION-INDUCED MATRIC SUCTION CHANGES IN UNSATURATED SOIL SLOPES - MOSISSA DAKSSA, LEMA (2014)
Bearing capacity calculations: slope stability analysis: lateral earth pressure calculations and contaminant transport predictions, among many others, are the key areas in geotechnical engineering where seepage modeling finds crucial applications. All these applications need to be implemented whether the soil is in a saturated or an unsaturated state. On the other hand, soil engineering properties change with changes in its moisture content. As the result, at macro-scale level, seepage through saturated soils is modeled using Darcy's law while Richards' equation is employed to model seepage through unsaturated soils.